2017
DOI: 10.1002/ijc.31127
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma recurrence according to race and ethnicity: An NRG Oncology/Gynecologic Oncology Group 210 Study

Abstract: Non-Hispanic black (NHB) women are more likely to experience an endometrial carcinoma (EC) recurrence compared to non-Hispanic white (NHW) women. The extent to which tumor characteristics, socioeconomic status (SES) and treatment contribute to this observation is not well defined. In the NRG Oncology/Gynecology Oncology Group (GOG) 210 Study we evaluated associations between race/ethnicity and EC recurrence according to tumor characteristics with adjustment for potential confounders. Our analysis included 3,19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…The motivations of this lack of treatment are multiple: barriers in the patient-physician communication, patient belief, and rejection of cancer [13]. Moreover, it has been observed that patients of black ethnicity have a lower overall survival compared to white women, tumor characteristics aside [14]. However, we did not find that patients of "other" race (such as Hispanics) were more likely to receive the incorrect treatment [4].…”
Section: Discussioncontrasting
confidence: 64%
“…The motivations of this lack of treatment are multiple: barriers in the patient-physician communication, patient belief, and rejection of cancer [13]. Moreover, it has been observed that patients of black ethnicity have a lower overall survival compared to white women, tumor characteristics aside [14]. However, we did not find that patients of "other" race (such as Hispanics) were more likely to receive the incorrect treatment [4].…”
Section: Discussioncontrasting
confidence: 64%
“…The association between BMI and endometrial cancer recurrence was investigated by fifteen studies. 63,[67][68][69]72,[74][75][76]78,[82][83][84]86,90,92 In a French Multicenter Study, Canlorbe et al 68 68 Moreover, none of the other studies that assessed the association between BMI and endometrial cancer recurrence observed a statistically significant relationship in the main 63,67,75,76,[82][83][84]90,92 or stratified analyses by endometrial cancer type, 69,78 tumour histological subtype, 72 or cancer stage. Two studies previously assessed the association between pre-diagnosis blood glucose levels and overall survival among endometrial cancer survivors, reporting no statistically significant associations.…”
Section: Recurrencementioning
confidence: 98%
“…Despite unclear mechanisms linking race with adjuvant treatment receipt, it is apparent that black women with EC continue to experience worse outcomes than their white counterparts (20, 34). In our NRG Oncology/GOG 210 Study population, black EC patients have significantly higher risks of all-cause mortality [hazard ratio (HR) =1.21], EC-specific mortality (HR=1.27), and recurrence risk (HR=1.36) (35).…”
Section: Commentmentioning
confidence: 99%